EFEKTIVITAS FLY TRAP TERHADAP Musca domestica - Riski Margareta; Widya Hary Cahyati (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
The exist of residential areas close to the Jatibarang landfill in Semarang City can cause the community to become susceptible to infection with diseases carried by house flies. So the need for vector control of house flies, one of which uses fly traps. The purpose of this study was to find the differences in the number of house flies trapped and the effectiveness of fly trap design and variations of bait that have been given. This type of research is a pre-experimental research with post-only design research design. The sample of this study was most house flies in residential areas around the Jatibarang Landfill. The results showed that the number of house flies trapped was 966. The number of house flies trapped in sugar-top water bottle fly trap is 27%, chicken meat top-water bottle fly trap is 22%, coffee top-water bottle fly trap is 14%, yellow sugar-water funnel bottle fly trap is 14%, fly trap bottle of funnel yellow-water chicken meat washing is 11%, fly trap bottle of funnel yellow-water coffee is 12%. The results concluded that the design of the top bottle fly trap with more sugar-water bait and effectively trap the house fly.Key words: Houseflies, Fly Trap, Bait